Green Cosmic Dreams: Utopia and Ecological Exile in Women's Exoplanetary Science Fiction - Middleton, Selena (My University, 2019)
Exile is not only an appropriate lens through which to view the ecological, social, and psychological destabilizations of the Anthropocene, but also as a state which can inspire the flexibility and creativity necessary to survive difficult times through ecologically-connected states of being. Examinations of literary alienation and responses to this condition in this project are confined to women’s exoplanetary science fiction which anticipates the experience of physical and emotional separation from planet Earth. In contextualizing experiences of exile from our planet of origin and the expressions of such in women’s science fiction literature, this project interrogates selected cultural movements in human relationships to the environment, separation from the environment, and resistances to that estrangement through the concept of exile. Chapter One considers the Western myth of the lost paradise and the ways in which the Garden of Eden has contributed to Western conceptions of environmental and human perfection and belonging and the persistent idea of working one’s way back to Eden. In contrast to this idea, I present analyses of James Tiptree Jr.’s A Momentary Taste of Being and Molly Gloss’s The Dazzle of Day, both of which illustrate that working toward perfection is an ultimately stagnating and often violent move. Chapter Two, mounting further challenges to the Western paradise and its reverberations through environmental discourse, frames science fiction’s initial acquiescence to narratives of colonization and later feminist rejection of these narratives. Analyzing the connections between colonial structures, the environment, and beings considered nonhuman or less-than-human in Ursula K. Le Guin’s The Word for World is Forest and Joan Slonczewski’s A Door Into Ocean, this chapter describes the psychological and emotional estrangements necessary to survive and resist colonization and its ecological destruction and contextualizes experiences of exile. Chapter Two argues that though exile is often a destructive process, it can form a basis with which to resist entrenched social structures. Finally, Chapter Three examines the ways in which Indigenous science fiction, working in a different historical and cultural context than that of the Western feminist texts discussed in the previous two chapters, emphasizes an experience of and approach to exilic destabilizations which centres on what Gerald Vizenor calls “survivance”—the survival of colonial genocide and resistance to further colonial impositions. While Lee Maracle’s “The Void” and Mari Kurisato’s “Imposter Syndrome” utilize exoplanetary distance from Earth’s ecosystems to illustrate modes of survivance, they also demonstrate the ways in which relations to the land are maintained through interrelational rather than hierarchical subjectivities, and demonstrate the resilience intrinsic to interconnected ecological systems. In sum, the estranged position of women’s exoplanetary science fiction emerges as critical of the hierarchical structures which have resulted in widespread ecological collapse, and imparts the perspective necessary not only to challenge those structures but also to survive their destabilizations.
Keywords: speculative fiction; science fiction; ecocriticism; feminism; ecology; climate change; anthropocene; indigenous literature